2003
DOI: 10.1186/1476-4598-2-31
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundThe hypoxia-inducible factor (HIF) transcription complex, which is activated by low oxygen tension, controls a diverse range of cellular processes including angiogenesis and erythropoiesis. Under normoxic conditions, the α subunit of HIF is rapidly degraded in a manner dependent on hydroxylation of two conserved proline residues at positions 402 and 564 in HIF-1α in the oxygen-dependent degradation (ODD) domain. This allows subsequent recognition by the von Hippel-Lindau (VHL) tumor suppressor protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…However, Pro582 has no essential role in HIF-1α stability because its mutation with serine does not affect HIF-1α levels, neither in normoxia nor hypoxia (Fig. 2 A ), which is in perfect agreement with previous observations (31). Moreover Pro582Ser does not have a central role in the destabilizing effect of glucose on HIF-1α (9) because we observed a clear destabilization of the Pro582Ser construct in hyperglycemia (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…However, Pro582 has no essential role in HIF-1α stability because its mutation with serine does not affect HIF-1α levels, neither in normoxia nor hypoxia (Fig. 2 A ), which is in perfect agreement with previous observations (31). Moreover Pro582Ser does not have a central role in the destabilizing effect of glucose on HIF-1α (9) because we observed a clear destabilization of the Pro582Ser construct in hyperglycemia (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Idiopathic erythrocytosis patients with a family history were selected from our registry (19,40). Ethical approval was obtained from the Queen's University Research Ethics Committee, and written, informed consent was obtained from all individuals.…”
Section: Methodsmentioning
confidence: 99%
“…A common SNP mapping in the ODD domain in exon 12 of HIF-1a (C1772T, Pro582Ser) has been described in the literature [13,29]. Although not involved in the process of hydroxylation [14], this SNP may confer susceptibility to renal cancerogenesis and progression. Supporting this hypothesis, Kim et al [8] showed that the Pro582Ser change contributes to the development of metastases.…”
Section: Discussionmentioning
confidence: 99%
“…This SNP leads to a proline to serine substitution at codon 582 [13,14]. Although C1772T has been shown not to affect the hydroxylation process [15], it might confer susceptibility to RCC and its presence has been demonstrated to correlate with the development of metastases [14]. Here, we evaluated the prognostic significance of such SNP in ccRCC patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation